Soil application of Trichoderma asperellum GDFS1009 granules promotes growth and resistance to Fusarium graminearum in maize - An-le HE; Jia LIU; Xin-hua WANG; Quan-guo ZHANG; Wei SONG; Jie CHEN (Journal of Integrative Agriculture, 2019)
Of diseases affecting maize (Zea mays), Fusarium graminearum is one of the most common pathogenic fungi that cause stalk rot. In the present study, the Trichoderma asperellum GDFS1009 strain was shown to be an effective biocontrol agent against stalk rot. In a confrontation culture test, Trichoderma strain displayed an approximately 60% inhibition rate on the mycelial growth of F. graminearum. In pot trials, the application of 2 g/pot of T. asperellum GDFS1009 granules had the best control effect on stalk rot at the seedling stage (up to 53.7%), while the average plant height and fresh weight were also significantly improved. Additionally when fertilizer was added at 8 g/pot, the application of 3 g/pot of Trichoderma granules had the best control effect on maize stalk rot (40.95%). In field trials, when inoculating F. graminearum alone, the disease index for inoculating was 62.45, but only 31.43 after treatment with T. asperellum GDFS1009 granules, suggesting a control efficiency of 49.67%. Furthermore, in a naturally F. graminearum-infected field, Trichoderma granules, when applied for 3 consecutive years, showed significant control of stalk rot and increased yields.